A Chemical Display: Generating Animations by Controlled Diffusion from Porous Voxels. (28th May 2015) - Kalinin, Yevgeniy V.; Pandey, Shivendra; Hong, Jinpyo; Gracias, David H.
<x xml:space="preserve">Abstract</x> The concept of utilizing precisely patterned and chemically loaded 3D porous containers akin to chemical voxels to enable dynamic visual patterns via spatial and temporal control of both local and global chemical release is described. Using numerical simulations and experiments, it is shown how variations in porosity, volume, shape, and relative positioning of the chemical voxels can be used to control the types of images that are formed with control in both space and time. Moving images are generated via controlled chemical release from an array of voxels to create an animation of a running man thereby illustrating proof‐of‐concept for a chemical display.